Kinetics of grain growth in Ti-2.7Al-5.7Fe-6Mo-6V alloy - Mutava, Tapiwa David; Cornish, Lesley Alison; Sigalas, Iakovos (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The metastable (βTi) alloy Ti-2.7Al-5.7Fe-6Mo-6V (wt%) was produced by semi-centrifugal casting of blended elemental powders. The phases were identified by X-ray diffraction (XRD), and overall composition was measured by X-ray fluorescence (XRF). The beta transus was determined by differential thermal analysis (DTA) and optical microscopy. The cast alloys were annealed at different temperatures under argon, up to 900oC, where they were in the solution-treated state, and the solution-treated alloys were aged between 400oC and 600oC. The kinetics of grain growth during heat treatment of the as-cast and solution-treated alloys was investigated by metallography, using the grain intercept method. Grain growth depended on whether the matrix was (αTi) or (βTi), and on the competing precipitate dissolution, or nucleation and growth processes. The as-cast alloy had a mean grain size of 19 ± 7µm, which increased to 63 ± 21µm after heat treating at 500oC for 2h. The alloy was duplex between 590oC and 800oC, and completely (βTi) above 800oC. After solution treatment, the mean grain size was 40 ± 16 µm, which was smaller than at the lower heat treatment temperatures. Following solution treatment, the mean grain size increased with increasing ageing temperature, up to 66 ± 22µm after 2h at 600oC. The growth exponents were lower than the 0.5 for normal grain growth in both cases, and there was an incubation period at 300oC and 400oC when the alloy was not solution-treated. Minimal grain growth was observed close to the beta transus.